2003
DOI: 10.1002/ange.200390220
|View full text |Cite
|
Sign up to set email alerts
|

Phospholane–Oxazoline Ligands for Ir‐Catalyzed Asymmetric Hydrogenation

Abstract: Eine neue Klasse chiraler Phospholan‐Oxazolin‐Liganden (P*) ermöglicht hohe Enantioselektivitäten in der Ir‐katalysierten asymmetrischen Hydrierung von Methylstilbenderivaten und (E)‐β‐Methylzimtsäureestern (siehe Schema; z. B. R=Ph, Ar=m‐CH3C6H4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Having been unsuccessful in generating an unsubstituted phospholane, we decided to try to further functionalize phospholane 8 a . Reactions at the α‐carbon of borane‐protected phosphanes (BisP*)28 and sulfur‐protected phospholanes (TangPhos)9b, 29 have been reported. However, when we applied the reported conditions to borane‐protected 8 a , no reaction was observed, regardless of the base or electrophile used.…”
Section: Resultsmentioning
confidence: 99%
“…Having been unsuccessful in generating an unsubstituted phospholane, we decided to try to further functionalize phospholane 8 a . Reactions at the α‐carbon of borane‐protected phosphanes (BisP*)28 and sulfur‐protected phospholanes (TangPhos)9b, 29 have been reported. However, when we applied the reported conditions to borane‐protected 8 a , no reaction was observed, regardless of the base or electrophile used.…”
Section: Resultsmentioning
confidence: 99%
“…A phospholane-oxazoline hybrid ligand was developed by Zhang et al for the Ir-catalyzed asymmetric hydrogenation of non-or less functionalized olefins (Scheme 3.65) [154]. Application of these ligands in the catalytic reaction gave good and excellent enantioselectivities (77-99 %ee.…”
Section: Bidentate Mono(phospholanes) Bearing a Second Ligating Non-pmentioning
confidence: 99%
“…Thus, using Crabtree's catalyst A as a conceptual template,4 Pfaltz and co‐workers pioneered the application of ligands with N,P‐coordinating groups57 in this area, particularly in phosphine oxazoline complexes like B 6. 814 Others,1416 including our group,17 subsequently designed and tested similar complexes. More recently, studies from our laboratories demonstrated that N ‐heterocyclic carbene–oxazoline ligands like C also could be used to reduce tri‐ and disubstituted arylalkenes with good conversions and enantioselectivities 18.…”
Section: Introductionmentioning
confidence: 99%